2016
DOI: 10.1021/acs.biochem.5b01127
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Bis(indolyl)-hydrazide–Hydrazone Derivatives as Potent Microtubule-Targeting Cytotoxic Agents against A549 Lung Cancer Cells

Abstract: The biological significance of microtubules makes them a validated target of cancer therapy. In this study, we have utilized indole, an important pharmacological scaffold, to synthesize novel bis(indolyl)-hydrazide-hydrazone derivatives (NMK-BH compounds) and recognized NMK-BH3 as the most effective one in inhibiting A549 cell proliferation and assembly of tissue-purified tubulin. Cell viability experiments showed that NMK-BH3 inhibited proliferation of human lung adenocarcinoma (A549) cells, normal human lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 59 publications
2
30
0
Order By: Relevance
“…Recently, indole derivatives bearing a carbohydrazide moiety have been found to exhibit potent anticancer, antibacterial, anti‐inflammatory, and antitubercular effects. Moreover, further studies of biological mechanisms have demonstrated that these derivatives can be targeted to inhibit signal proteins, such as β‐glucuronidase, Akt1, CYP1AY, and microtubules …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, indole derivatives bearing a carbohydrazide moiety have been found to exhibit potent anticancer, antibacterial, anti‐inflammatory, and antitubercular effects. Moreover, further studies of biological mechanisms have demonstrated that these derivatives can be targeted to inhibit signal proteins, such as β‐glucuronidase, Akt1, CYP1AY, and microtubules …”
Section: Introductionmentioning
confidence: 99%
“…Moreover,f urthers tudies of biological mechanisms have demonstrated that these derivatives can be targeted to inhibit signal proteins, such as b-glucuronidase, [30] Akt1, [31] CYP1AY, [32] and microtubules. [33] We have succeeded in using as tructure-based approach to discover ac lass of quinazolined erivatives that inhibitt he VEGFR-2 protein. [34] In this study,w ea ttempted to develop indole-2-carbohydrazide derivativesa sa nti-angiogenesis agents.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of NMK-BH3 in NSCLC (A549 cells) revealed the disruption of the mitotic spindle and depolymerization of the interphase microtubule network ultimately led to apoptotic cell death. This is signified by the overexpression of Bax, p53, caspase 3, and caspase 9 and decrease in the Bcl-2 expression [80]. Their experiments revealed that NMK-BH3 was more sensitive to human lung adenocarcinoma A549 cells with IC 50 of~2 µM, while highly resistant to normal human lung fibroblasts (WI38) with IC 50 of 48.5 µM (24 fold).…”
Section: Tubulin Inhibitionmentioning
confidence: 99%
“…The synthesis of NMK-BH3 was achieved as shown in Scheme 7 [80]. A solution of indole-2carboxylic acid (42)…”
Section: Inhibition Of Dna-topoisomerasesmentioning
confidence: 99%
“…21–23 Inspired by the fascinating anticancer properties of β- carbolines and azolium salts, in this paper we designed a diverse series of β- carbolinium salts by incorporating remarkable features of β- carboline and 1-aryl-2-bromoethanones in single molecule as depicted in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%